AS CONEXÕES DO MARANHÃO COM A ÁFRICA NO TRÁFICO ATLÂNTICO DE ESCRAVOS NA SEGUNDA METADE DO SÉCULO XVIII - Meireles, Marinelma Costa (Outros Tempos: Pesquisa em Foco - História, 2009)
This article approaches the connections of the Maranhão with Africa in the second half of century XVIII, when of the implantation of the General Company of Grão-Pará and Maranhão, and this commercial enterprise got the monopoly of the commerce of African slaves for the maranhense region.